PESONA HERBAL SEBAGAI UPAYA MENGEMBANGKAN ECO-EDUCATION DAN KEWIRAUSAHAAN PRODUK OLAHAN HERBAL - Suryadarma, IGP; Widowati, Asri; Mustofa, Mustofa (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2013)
The activity "The Beauty of Herb" is aimed: (1) to improve the understanding of mother and young man about kinds of herb ans its usefulness; (2) to improve the creativity of mother and young man about way of processing of herb; (3) to improve enterpreneurship of mother and young man. The methods used in trouble-shooting covers: nature exploration, discourse, demonstration and practise. Its steps cover: motivation phase, phase training of theory, and phase training of practise. Data are collected by using quesionare and observasion sheet. Argomulyo's mother and young man respond well by involving actively in every activity phase. This training have earned to improve the understanding of participants about herb ang usefulness. Participant have skill process to process the herbs as products which are prospective They also recognize herbs' product as a business opportunity and intend to plant and propagate herb to others as eco-education.Keywords: The Beauty ofHerb, enterpreneurship, and eco-education